Perbandingan status koagulasi penderita stroke iskemik dengan non stroke - Zainal Abdi; Rusli Dhanu; Savita Handayani; Dairion Gatot (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Background: Thrombosis is one of causes increasing morbidity, disablement,and mortality in ischemic stroke’s patient. The basic mechanism of thrombosis is hypercoagulation state, so by finding it earlier can prevent and reduce thrombosis that cause ischemic stroke.Objective: This study to asses the event of hypercoagulation between ischemic stroke’s patient and non stroke. Methods: A total of 21 subjects with ischemic stroke’s patient and 21 subjects with non stroke entered into the study. All participants were examined for hemostatic parameters included prothrombin time (PT), INR, activated partial thromboplastin Time (aPTT), Fibrinogen, D-dimer. To compare the result of hemostatic both of groups were used t independent test if the distribution was normal or used Mann Whitney test if the distribution wasn’t normal. The result would be significant if P <0.05. Result: According to characteristic of population, it was found some variables significantly, included systolic blood pressure, diastolic blood pressure, INR, aPTT ratio and D-dimer. Hypercoagulation in ischemic stroke group was found 47.6% (n=10) and non hypercoagulation group was 52.4% (n=11) , but in non stroke group, hypercoagulation was found about 23.8% (n=5) and non hypercoagulation was 76.2% (n=16). According to statistical analysis there wasn’t significant hypercoagulation between ischemic stroke’s patient and non stroke (P >0.05).Conclusion: There isn’t significant hypercoagulation between ischemic stroke group with non stroke group. Keywords: ischemic stroke; hemostatic measurement; hypercoagulation; thrombosis